Strategi Perawatan Mesin Di Line Sabroe Menggunakan Metode RCM Dan MVSM Di PT XYZ - Nanda Firlana; Joumil Aidil (Jurnal Kendali Teknik dan Sains, 2023)
This study aims to analyze the RCM (Reliability Centered Maintenance) and MVSM (Maintenance Value Stream Mapping) strategies implemented by PT. XYZ in machine maintenance at the Sabroe Line. RCM is used to reduce equipment failures and ensure that each physical item or system is functioning as intended. Meanwhile, MVSM is used to identify waste in maintenance activities and perform repair analysis. The research method used is qualitative research with a case study approach. Data was collected through observation, interviews and analysis of related documents. The results of the research show that PT. XYZ has implemented the RCM and MVSM strategies effectively in engine maintenance at the Sabroe Line. RCM implementation helps to reduce machine failure and increase machine reliability. Meanwhile, MVSM helps identify and overcome waste in maintenance activities. In conclusion, the RCM and MVSM strategies are effective approaches in engine maintenance at the Sabroe Line. This research provides a better understanding of the importance of a planned and structured maintenance strategy in improving engine performance. The recommendation for future research is to involve more departments and measure the impact of RCM and MVSM strategies on overall operational productivity and efficiency.